1989
DOI: 10.1042/bj2610985
|View full text |Cite
|
Sign up to set email alerts
|

Hormone and substrate regulation of glycogen accumulation in primary cultures of rat hepatocytes

Abstract: Hormonal and substrate regulation of hepatic glycogen accumulation was evaluated in primary cultures of hepatocytes prepared from 1-day-fasted rats. Hepatocytes were cultured in media containing 5 mM-glucose and 10 mM-lactate and then exposed to 100 nM-dexamethasone for 4 h before an increase in glucose concentration and the addition of insulin. When this protocol was used to mimic the post-prandial state in vivo, net glycogen accumulation (over 2 h) and insulin (10 nM) effects were linear at physiological (5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Findings over the last decade indicate that in the postprandial phase glucose is not directly incorporated into hepatic glycogen but is first degraded to C3 compounds, presumably in lactate, the site of lactate formation (hepatic or extrahepatic) remaining to be established (for reviews, see Katz & McGarry, 1984;Pilkis et al, 1985;McGarry et al, 1987). Studies on cultured adult (Spence & Koudelka, 1985;Parniak & Kalant, 1985;Salhanick et al, 1989) and foetal (Bismut & Plas, 1989) rat hepatocytes have shown that the classical direct pathway of glucose incorporation into glycogen functions concomitantly with an indirect one mediated by triose phosphate formation, and that both direct and indirect pathways are stimulated by insulin. As regards foetal hepatocytes, the indirect pathway, which involves one-third of the glucose used for glycogen synthesis, is not mediated by the formation of pyruvate-derived metabolites (Bismut & Plas, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Findings over the last decade indicate that in the postprandial phase glucose is not directly incorporated into hepatic glycogen but is first degraded to C3 compounds, presumably in lactate, the site of lactate formation (hepatic or extrahepatic) remaining to be established (for reviews, see Katz & McGarry, 1984;Pilkis et al, 1985;McGarry et al, 1987). Studies on cultured adult (Spence & Koudelka, 1985;Parniak & Kalant, 1985;Salhanick et al, 1989) and foetal (Bismut & Plas, 1989) rat hepatocytes have shown that the classical direct pathway of glucose incorporation into glycogen functions concomitantly with an indirect one mediated by triose phosphate formation, and that both direct and indirect pathways are stimulated by insulin. As regards foetal hepatocytes, the indirect pathway, which involves one-third of the glucose used for glycogen synthesis, is not mediated by the formation of pyruvate-derived metabolites (Bismut & Plas, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin is among the hormones that regulate the concentration of glycogen in peripheral organs (Stalmans et al, 1987;van de Werve and Jeanrenaud, 1987). In cultured hepatocytes, insulin enhances glycogen synthesis and reduces the activity of glycogen phosphorylase (Schudt, 1979(Schudt, , 1980Hartmann et al, 1987;Salhanick et al, 1989). Brain contains insulin-like peptides, including insulin-like growth factor (IGF) I (for reviews, see Baskin et al, 1987Baskin et al, , 1988Wood et al, 1989), as well as the corresponding receptors (Roth et al, 1986;Rosenfeld et al, 1987).…”
mentioning
confidence: 99%
“…5) and most of previous literature (Lopez et al, 1984; Yang et al, 2009) confirm the insensitivity of hepatocytes in monolayer and sandwich culture to the hormone stimulation. It was also been noted that, in the few reports where positive hormonal regulation was shown, a short preincubation time (18–24 h) and an extremely high concentration (1,000–100,000‐folds higher than physiological level) of glucagon (Walker and Grindle, 1977) or dexamethasone (Salhanick et al, 1989) were needed to regulate glycogen in hepatocytes. The low sensitivities of hepatocyte monolayers were partially attributed to the loss of hepatic functions, such as decreased glucose metabolism enzymes (Walker and Grindle, 1977) and insulin‐response receptor (Hansson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%